A Study of the Relationship between Stress and Mental Health of Students at Naresuan University During the Spread of the Covid-19 - Anusaksathien, Kantabhat (Journal of Social Sciences Naresuan University, 2024)
The purposes of this research were to study the relationship between stress and mental health status of Naresuan University students during the outbreak of the Coronavirus 2019. It was a survey with a sample of 550 students conducted online by using a personal information questionnaire, the Suanprung Stress Test-20 and the Thai General Health Questionnaire. The results showed that most of the students in this study, 207 out of 550, were moderately stressed (average of 34.71) and, 166 out of 550, had mental health problems (average of 12.51). The most students had mental health problems of anxiety and insomnia followed by physical symptoms, severe depression, and social disability. From the study of the differences in stress and mental health classified by personal factors, it was found that different gender, age level and average monthly income had no correlation with stress and mental health. The study also found that stress and mental health problems had a statistically significant positive relationship at the .01 level during the outbreak of the Covid-19. In conclusion, the Covid-19 had an effect on stress and mental health of Naresuan University students with a moderate positive correlation with statistical significance at the .01 level.